2014
DOI: 10.7314/apjcp.2014.15.3.1351
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Sex Cord Stromal Tumours in Children and Young Girls - A More Than Two Decade Clinicopathological Experience in a Developing Country, Pakistan

Abstract: Background: Ovarian sex-cord stromal tumours (SCST) are rare, and relatively infrequent in children. These have to be distinguished from more common germ cell tumors in children and also from benign epithelial neoplasms. Objectives: The purpose of our study was to report the clinical and pathological findings in young patients with these tumours in our population. Material and Methods: The present observational cross-sectional study included all subjects <21 years of age diagnosed with ovarian SCST, in Aga Kha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…This is in accordance with the available international literature. [6][7][8][9] The histomorphological observations in our study are similar to other reports. 6,7 We observed that most of the tumors were unilateral, ranging from 5 to 15 cm in size.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with the available international literature. [6][7][8][9] The histomorphological observations in our study are similar to other reports. 6,7 We observed that most of the tumors were unilateral, ranging from 5 to 15 cm in size.…”
Section: Resultssupporting
confidence: 90%
“…We encountered one case of sex cord tumor with annular tubules. The percentage of Juvenile Granulosa cell tumors was more than that observed by Cartault et al and Scheneider et al while similar to those reported by Haroon et al 4,9,10 However, sertoli leydig cell tumors was found to be less frequent than fibrothecoma group as compared to those in other studies. 6,7 This could be due to reluctance of patients with symptoms of virilization to come for treatment due to social stigma attached.…”
Section: Resultssupporting
confidence: 87%
“…In contrast, we found only one from 48 cases (2.1%) which had sex cord-stromal tumor, whereas the report by Brookfield et al showed 5.7% (Brookfield et al, 2009) and another study by Hassan et al showed 12.3% of 57 cases (Hassan et al, 1999). In Asia, Haroon et al from Pakistan reported 39 cases of ovarian sex cord-stromal tumor in children and young girls from their 20 year-experience (Haroon et al, 2014). These discrepancies may derive from the limitation of our data and the large number of patients in other studies may be deviated from the percentages of outcomes.…”
Section: Discussionmentioning
confidence: 68%
“…Polycystic ovary syndrome (PCOS) is a proliferative disorder among women of reproductive age, and currently considered a predominantly hyperandrogenic syndrome (Azziz et al, 2009;Bilici et al, 2013;, Haroon et al, 2014;Liu et al, 2013;Takiar et al, 2014a;2014b). The three main diagnostic guidelines are the 1990 National Institutes of Health (NIH) criteria (Dunaif, 1992) T2DM is a disease characterized by impaired insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%